PENGARUH PEMBERIAN EKSTRAK DAUN KELOR (Moringa oleifera) TERHADAP KADAR KOLESTEROL HDL TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR HIPERGLIKEMIA DENGAN INDUKSI ALOKSAN - Lybelary Dewi Satrianawaty; Tri Martini Sumarno; Sulistiana Prabowo (Universitas Hang Tuah, 2019)
ABSTRACT Background : Diabetes mellitus (DM) is a chronic metabolic syndrome characterized by an increase in blood glucose levels due to a lack of insulin, less effective insulin action or both. Hyperglycemia can cause a decrease in HDL cholesterol. Alloxan can reduce HDL cholesterol due to the mechanism of ROS formation. Moringa contains antioxidants that can prevent oxidative stress so that it is expected to increase HDL cholesterol levels. Method : This study used 24 male Wistar rats divided into 3 groups. The first group was given standard feed without alloxan induction, the second group was induced by 150 mg/kgBW intraperitoneal alloxan in the first day, and the third group was induced by alloxan in the first day and given 600 mg/kgBW Moringa leaf extract for 14 days begining at the fourth day. At the end of the study a serum HDL cholesterol levels were measured in each group.Result : One Way Anova test results showed significant decrease of serum HDL cholesterol (p = 0.024) in the alloxan-induced animal group (x = 26.88 mg/dL) compared to the group of rats fed with standard feed without alloxan induction (x = 33.13 mg/dL). There was no significant increase (p = 0.174) of HDL cholesterol in the group of rats that were induced by alloxan and given Moringa leaf extract (x = 29.25 mg/dL) compared to the group of rats that were induced by alloxan without being given Moringa leaf extract (x = 26, 88 mg/gL).Conclusion : this study showed that alloxan significantly reduced serum HDL cholesterol levels and the administration of Moringa leaf extract tended to increase serum HDL cholesterol levels in white rats induced by alloxan because flavonoids and phenols in Moringa leaves acted as antioxidants, but the increase was not statistically significant.